University environmental performance in the UI Green Metric Ranking: case of Costa Rican Institute of Technology, central technological campus - Rodríguez Rodríguez, Alina (2021)
Since 1995, Costa Rican Institute of Technology has promoted the development of various projects in order to achieve the sustainability in the activities made inside and outside of its facilities. Thanks to the vision and work of many officials and students, today the Institution is internationally recognized for being the first Costa Rican public university to achieve the carbon neutrality,  also to declare itself free of single-use plastic, design and build its own solar farm and to promote sustainable mobility through the development of an automated bicycle loan system. These projects, together with other measures implemented, allowed it in 2018 to apply in the IU Green Metric World University Ranking, where were evaluated criteria such as: setting and infrastructure; energy and climate change; waste; water; transportation; education and research. In 2019, Costa Rican Institute of Technology advance 61 positions, becoming the most sustainable university in Central America.